2022
DOI: 10.3390/su141711056
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Intensification of Rice Fallows with Oilseeds and Pulses: Effects on Soil Aggregation, Organic Carbon Dynamics, and Crop Productivity in Eastern Indo-Gangetic Plains

Abstract: Climate-smart agriculture (CSA) practices are becoming increasingly important due to their better adaptability to harsh climatic conditions (in general) and the unpredictability of monsoons in India (in particular). Conventional rice cultivation (e.g., PTR) involves intensive tilling followed by intensive puddling in standing water that destroys the soil aggregation and depletes carbon pools. Therefore, alternative crop establishment methods need to be devised for the sustainability of system productivity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Factors such as soil health, water usage, GHG emissions, and long-term sustainability should be evaluated to make more comprehensive conclusions about the benefits and trade-offs of different tillage methods. Taking those into account, MT emerges as the superior tillage approach since it maintains soil health, is cost-effective, and yields outcomes on par with those of CT practices in the short term while after stabilization ZT can potentially improve the system's performance [ 26 , 39 ]. This experiment showed that live mulching had the highest net energy and energy output.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as soil health, water usage, GHG emissions, and long-term sustainability should be evaluated to make more comprehensive conclusions about the benefits and trade-offs of different tillage methods. Taking those into account, MT emerges as the superior tillage approach since it maintains soil health, is cost-effective, and yields outcomes on par with those of CT practices in the short term while after stabilization ZT can potentially improve the system's performance [ 26 , 39 ]. This experiment showed that live mulching had the highest net energy and energy output.…”
Section: Discussionmentioning
confidence: 99%
“…Some research is descriptive in nature rather than constituting a thorough critical analysis of the studies under examination [18][19][20][21][22]. Other ones are quantitative, but there is no comprehensive approach in terms of combining the multiple aspects of the problem, including hydrology, social, and economic aspects [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Rice (Oryza sativa L.), largely cultivated by transplanting in rainfed conditions during the southeast monsoon season, is a staple food crop of the eastern region of India. Puddling, i.e., tillage in standing water, is extensively practiced for rice transplanting, which minimizes percolation losses, suppresses weed growth and improves plant nutrient availability [5]. However, puddling is known to degrade the soil health by the formation of hardpan in the sub-soil, destroying soil aggregation and decreasing the population of beneficial microorganisms, thus reducing crop yields of subsequent post-rainy crops in ricefallows [6].…”
Section: Introductionmentioning
confidence: 99%